Direct Anandamide Activation of TRPV1 Produces Divergent Calcium and Current Responses - Fenwick, Axel J.; Fowler, Daniel K.; Wu, Shaw-Wen; Shaffer, Forrest J.; Lindberg, Jonathan E. M.; Kinch, Dallas C.; Peters, James H. (Frontiers in Molecular Neuroscience, 2017)
In the brainstem nucleus of the solitary tract (NTS), primary vagal afferent neurons express the transient receptor potential vanilloid subfamily member 1 (TRPV1) at their central terminals where it contributes to quantal forms of glutamate release. The endogenous membrane lipid anandamide (AEA) is a putative TRPV1 agonist in the brain, yet the extent to which AEA activation of TRPV1 has a neurophysiological consequence is not well established. We investigated the ability of AEA to activate TRPV1 in vagal afferent neurons in comparison to capsaicin (CAP). Using ratiometric calcium imaging and whole-cell patch clamp recordings we confirmed that AEA excitatory activity requires TRPV1, binds competitively at the CAP binding site, and has low relative affinity. While AEA-induced increases in peak cytosolic calcium were similar to CAP, AEA-induced membrane currents were significantly smaller. Removal of bath calcium increased the AEA current with no change in peak CAP currents revealing a calcium sensitive difference in specific ligand activation of TRPV1. Both CAP- and AEA-activated TRPV1 currents maintained identical reversal potentials, arguing against a major difference in ion selectivity to resolve the AEA differences in signaling. In contrast with CAP, AEA did not alter spontaneous glutamate release at NTS synapses. We conclude (1) AEA activation of TRPV1 is markedly different from CAP and produces different magnitudes of calcium influx from whole-cell current, and (2) exogenous AEA does not alter spontaneous glutamate release onto NTS neurons. As such, AEA may convey modulatory changes to calcium-dependent processes, but does not directly facilitate glutamate release.